Ritual Sweat Bath in a Cross-Cultural Perspective - Wójtowicz-Wcisło Marta (Open Theology, 2023)
This article traces differences and similarities in the ritual sweat bath usage through a comparative perspective that includes contemporary practice in Poland and the central and the north American traditions that inform it. I argue that there exist continuity and consistency of representations related to sweat bathing across time and space, which can be identified by the metaphors designating certain elements of the ritual. The bathhouse from a cross-cultural perspective can be considered a sacred and liminal space, a gateway that enables the transcending of ordinary space–time dimension and interaction with primordial creation–destruction forces. Fertility appears as only one aspect of these ambivalent forces. It manifests itself in the main metaphors of the Mother Earth’s womb and death–rebirth process in ritual’s contemporary descriptions in Poland. The similarities in the way the sweat bath experience is conceptualised reveal the influence of particulr elements of the ritual that induce specific bodily sensations, intrinsically related to the human organism conditions.